Random copolyesters containing perylene bisimide: flexible films and fluorescent fibers - Nisha, S. Kumari; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Random copolyesters of poly(L-lactic acid) (PLLA) and [poly-(1,4-cyclohexylenedimethylene-1,4- cyclohexanedicarboxylate)] (PCCD) incorporating varying mol ratios of perylene bisimide (PBI) were developed via a high-temperature solution-blending approach. PCCD incorporating PBI was developed by melt polycondenzation followed by a polyester-polyester transesterification reaction between PCCD PBI and PLLA. The polymers exhibited good solubility in common organic solvents and formed free-standing films, which showed bright red emission upon irradiation with ultraviolet radiation. A solid state fluorescence quantum yield of 10% was observed for this PBI based polyester, which was much higher than that reported in literature for PBI based polymers in the solid state (<1%). Strong red fluorescent nanofibers of these polymers were successfully constructed by electrospinning technique. A random copolyester incorporating donor based on oligo(p-pheneylenevinylene) (OPV) and PBI as acceptor chromophore was also synthesized and fluorescence microscopy images of the electrospun fibers of this polymer exhibited blue, green and red emission upon excitation at different wavelengths. The high temperature solution blending approach involving a high molecular weight polymer and a suitably functionalized it conjugated molecule described here is a unique method by which 1D nanostructures of a wide range of pi-conjugated chromophores could be fabricated having strong fluorescence, with the scope of application in nanoscale optoelectronics, biological devices, as well as sensing.
Keywords: flexible film; fluorescent nanofibers; luminescent film; oligo(p-phenylenevinylene); perylene bisimide